Mapping the distribution of serotonin transporter in the human brainstem with high-resolution PET: Validation using postmortem autoradiography data - Fazio, P.; Schain, M.; Varnäs, K.; Halldin, C.; Farde, L.; Varrone, A. (NeuroImage (Orlando, Fla.), 2016)
The human brainstem is a complex structure with several small nuclei and neural pathways of interest in the pathophysiology of central nervous system (CNS) disorders. In common with other monoaminergic systems, serotoninergic neurons originate from a group of nuclei located in the brainstem. The present study was designed to validate a user-independent approach for a detailed in vivo quantification of serotonin transporter (5-HTT) availability in the human brainstem using a template-based approach that consisted of three steps. First, 3T-MR images and parametric binding potential (BPND) [11C]MADAM images of ten healthy subjects were used to generate a PET template of 5-HTT availability. In the second step, volumes of interest (VOIs) for different brainstem nuclei were obtained using a method in which VOIs are initially delineated on MRI images using anatomical landmarks and then are finally tailored on the distribution of 5-HTT binding using a thresholding approach applied to the 5-HTT template. In the final step, the VOIs were transformed and applied individually to BPND images of 16 healthy subjects (14M/2F, 20–64years). The in vivo distribution of BPND values obtained with the template-based method were in good agreement with an individual-based approach taken as gold standard. Results were also in agreement with 5-HTT quantification using in vitro binding data obtained with autoradiography (ARG) studies using [3H]MADAM. The proposed template-based method can be applied to PET data acquired in several CNS disorders in which serotonin neurons in the brainstem might be affected. •A detailed in vivo brainstem quantification of serotonin transporter availability (5-HTT) is proposed.•A user independent template based approach allows reliable quantification in 5-HTT enriched nuclei along the brainstem.•Detailed in vivo quantification of brainstem monoaminergic targets can provide a set of useful information in CNS disorders.